Formulation and quality assessment of biscuits fortified with galactagogue-rich ingredients for lactating mothers - Kohinur Akter; Monirul Islam; Md. Rakibul Hasan; Md. Faridul Islam; Md. Azizul Haque; Md. Mahbubul Bashar; Md. Ahiduzzaman; M. Burhan Uddin; Rokeya Begum (Applied Food Research)
The study reveals the development and quality evaluation of biscuits that enriched with galactagogue effects for lactating mothers. Natural galactagogue mix was formulated using food ingredients like moringa leaf (10 %), moringa pod (40 %), black cumin seed (10 %), and cashew nuts (40 %). Composite flour of wheat and galactagogue mix powder were blended ( %, w/w) at ratios of 100:0, 95:5, 90:10, 85:15, and 80:20, where 100:0 ratio refers to as control. Incorporation of galactagogue mix into wheat flour significantly (p < 0.05) increased protein, fat, fiber, and ash while decreased moisture content and carbohydrates than wheat flour. In addition, significant increases in water absorption capacity ( %), emulsion capacity %, and emulsion stability ( %) was observed, while oil absorption capacity ( %), foaming capacity ( %), foaming stability ( %), swelling capacity, and density of mix were significantly (p < 0.05) decreased. The thermal stability of the mix was higher than that of wheat flour, but lower than the composite flour. FTIR spectroscopy revealed the presence of lactogenic compounds in the mix, including saponins and phytoestrogens, which were partially retained in composite flour and biscuits. The biscuits were also analyzed for some physical properties, antioxidant activity, phenolic content, and sensory attributes. Biscuits fortified with composite flour significantly (p < 0.05) increased the amount of protein (9.01 % to 13.78 %), antioxidant activity (1.77 % to 2.65 %), and total phenol content (4.74 mg GAE/g to 9.92 mg GAE/g). Sensory evaluation indicated that biscuits with 10 % galactagogue mix were most acceptable. This study indicated the potential of developing functional foods for lactating mothers.